Nanoshell-mediated photothermal therapy can enhance chemotherapy in inflammatory breast cancer cells - Fay BL; Melamed JR; Day ES (International Journal of Nanomedicine, 2015)
Brittany L Fay, Jilian R Melamed, Emily S Day Biomedical Engineering, University of Delaware, Newark, DE, USA Abstract: Nanoshell-mediated photothermal therapy (PTT) is currently being investigated as a standalone therapy for the treatment of cancer. The cellular effects of PTT include loss of membrane integrity, so we hypothesized that nanoshell-mediated PTT could potentiate the cytotoxicity of chemotherapy by improving drug accumulation in cancer cells. In this work, we validated our hypothesis using doxorubicin as a model drug and SUM149 inflammatory breast cancer cells as a model cancer subtype. In initial studies, SUM149 cells were exposed to nanoshells and near-infrared light and then stained with ethidium homodimer-1, which is excluded from cells with an intact plasma membrane. The results confirmed that nanoshell-mediated PTT could increase membrane permeability in SUM149 cells. In complementary experiments, SUM149 cells treated with nanoshells, near-infrared light, or a combination of the two to yield low-dose PTT were exposed to fluorescent rhodamine 123. Analyzing rhodamine 123 fluorescence in cells via flow cytometry confirmed that increased membrane permeability caused by PTT could enhance drug accumulation in cells. This was validated using fluorescence microscopy to assess intracellular distribution of doxorubicin. In succeeding experiments, SUM149 cells were exposed to subtherapeutic levels of doxorubicin, low-dose PTT, or a combination of the two treatments to determine whether the additional drug uptake induced by PTT is sufficient to enhance cell death. Analysis revealed minimal loss of viability relative to controls in cells exposed to subtherapeutic levels of doxorubicin, 15% loss of viability in cells exposed to low-dose PTT, and 35% loss of viability in cells exposed to combination therapy. These data indicate that nanoshell-mediated PTT is a viable strategy to potentiate the effects of chemotherapy and warrant further investigation of this approach using other drugs and cancer subtypes. Keywords: nanoshells, photothermal therapy, hyperthermia, chemotherapy, sensitization, breast cancer